Fluency or Accuracy - Two Different Colours in Writing Assessment - Listyani, Listyani (LLT Journal: A Journal on Language and Language Teaching, 2016)
Fluency and accuracy. These two things have victoriously won many teachers attention at tertiary level. In the case of writing, these two remain debatable, and have always attracted many people, both lecturers and students attention. These language production measures have distracted many lecturers concentration: should they be faithful to fluency of ideas, or grammatical and language accuracy in correcting students essays? This paper tries to present the classical yet never-ending dilemmatic conflicts within the area of writing assessment. This debate still remains interesting to follow. Data were gained from close observation on documents, that is, 21 students essays and interviews with 2 students of Academic Writing in Semester II, 2015-2016. Four writing lecturers were also interviewed for their intellectual and critical opinions on these dilemmatic problems in assessing writing. Discussion results of FGD (Forum Group Discussion) involving all writing lecturers at the English Education Study Program at the Faculty of Language and Literature of Satya Wacana Christian University which were held in June, 2016, were also included as source of data. Hopefully, this paper gives a little more colour in the area of writing assessment, and gives a little enlightenment for other writing lecturers.